STUDY OF FORCE DEPENDENCES IN DIAMOND IRONING (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The article considers the force dependences during diamond ironing at the beginning of movement with various mandrels, in contrast to a mandrel with a rigid structure: a pneumatic mandrel and a pneumatic mandrel on springs.